Identifying environmental factors that influence immune response to SARS-CoV-2: Systematic evidence map protocol. (June 2022) - Rayasam, Swati D.G.; Aung, Max T.; Cooper, Courtney; Kwiatkowski, Carol; Germolec, Dori R.; Rooney, Andrew A.; Walker, Vickie R.; Forte, Chanese; Woodruff, Tracey J.; Chartres, Nicholas
Abstract: Background: Widespread environmental contamination can directly interact with human immune system functions. Environmental effects on the immune system may influence human susceptibility to respiratory infections as well as the severity of infectious diseases, such as the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Furthermore, the efficacy of vaccines to respiratory diseases may be impacted by environmental exposures through immune perturbations. Given the quick pace of research about COVID-19 and associated risk factors, it is critical to identify and curate the streams of evidence quickly and effectively. Objective: We developed this systematic evidence map protocol to identify and organize existing human and animal literature on high-priority environmental chemical classes (Per- and polyfluoroalkyl substances, pesticides, phthalates, quaternary ammonium compounds, and air pollutants) and their potential to influence three key outcomes: (1) susceptibility to respiratory infection, including SARS-CoV-2 (2) severity of the resultant disease progression, and (3) impact on vaccine efficacy. The result of this project will be an online, interactive database which will show what evidence is currently available between involuntary exposures to select environmental chemicals and immune health effects, data gaps that require further research, and data rich areas that may support further analysis. Search and study eligibility: We will search PubMed for epidemiological or toxicological literature on select toxicants from each of the chemical classes and each of the three outcomes listed above. Study appraisal and synthesis of methods: For each study, two independent reviewers will conduct title and abstract screening as well as full text review for data extraction of study characteristics. Study quality will not be evaluated in this evidence mapping. The main findings from the systematic evidence map will be visualized using a publicly available and interactive database hosted on Tableau Public.